Motivação e multiletramentos críticos na aprendizagem de língua inglesa - Perine, Cristiane Manzan (2019)
The purpose of this study is to investigate the possible implications of the critical multiliteracies approach to English language learning as well as to students’ motivation to learn in public education. We understand critical multiliteracies in a historical-cultural perspective as a practice social. It address the complexity of meaning making and knowledge building in contemporary society, where communication is increasingly multimodal and permeated by digital resources. Our theoretical framework is based on critical literacy and multiliteracies studies (COPE; KALANTZIS, 2012, MONTE MÓR, 2015, MORRELL, 2015, ROWSELL, 2016). We also rely on motivation in language learning as an aspect that plays a crucial role in learning a foreign language as a "person in context," rather than a simple "learner," seeing as an abstract and non-personalized agent. Therefore, motivation is understood as a dynamic, contextual, situational, temporal and multifaceted construct (KIM, 2009; BENESH, 2013; USHIODA, 2013; DÖRNYEI, 2014; KUBANYIOVA, 2018). Hence, motivation is an organic process that emerges through a complex system of interrelations. Thus, in this study, we relate the critical multiliteracies perspective and students’ motivation to learn English at an elementary public school. The research context is a federal school in the state of Minas Gerais. In this qualitative study, the data were collected through questionnaires, a learning narrative, field notes, recordings and transcription of classes and activities developed by the students. The results of the data analysis show that students enjoy learning English and that English is present in their daily lives, whether through formal or informal experiences. A number of challenges are faced by the teachers when adopting a critical multiliteracies approach, as the need to learn how to take advantage of the opportunities that arise routinely to explore critique and work within their contextual possibilities and limitations. In addition to contributing to students' motivation, such a teaching approach reveals broad possibilities for students to re-signify the process of English language learning, to expand their interpretive capacity, to develop their critique in their world readings and, above all, to improve their linguistic knowledge. By relating motivation and critical multiliteracies in English language learning, it is possible to create a path to motivate the learner to learn and appropriate the language as a means of reflection and action, but to act in a wider social context, not restricted to the educational environment. In this way, the results of the research can lead to reflections on the role of English language teaching in the globalized world aiming at the formation of the learner as a critical, reflective and participatory citizen who seeks to understand and continually question the world around him.